2018
DOI: 10.4081/ijfs.2018.7167
|View full text |Cite
|
Sign up to set email alerts
|

Kebab: can the traditional cooking process sanitize a natural contamination by Listeria monocytogenes?

Abstract: Over the last few years a considerable spread of ethnic foods was observed in Italy. Among them is the Döner kebab. During 2014-2015, in order to evaluate the effectiveness of traditional cooking process, raw product (defrosted), sliced cooked portions cut through electric knife and assembled sandwich were officially sampled in kebab houses and in a local industrial kebab producer in Reggio Emilia (a province in Italy). Microbiological researches for safety and hygienic microbiological indicators were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
3
1
1
Order By: Relevance
“…All of the isolates showed susceptible (100%) to chloramphenicol, contrary to the study conducted by Beyi et al (2017) that reported the resistance of E. coli to chloramphenicol. Chloramphenicol is bacteriostatic for Gram-positive bacteria and Gram-negative bacteria.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…All of the isolates showed susceptible (100%) to chloramphenicol, contrary to the study conducted by Beyi et al (2017) that reported the resistance of E. coli to chloramphenicol. Chloramphenicol is bacteriostatic for Gram-positive bacteria and Gram-negative bacteria.…”
Section: Discussioncontrasting
confidence: 86%
“…Using low-quality raw meat and under cooked meat may cause food safety issues in kebab (Ergonul et al, 2012). Escherichia coli was one of the bacteria that was related to foodborne disease in kebab (Bonilauri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In traditional kebab restaurants, the döner kebab cone is grilled on its outer surface on a vertical rotating spit. When the first outer layer is sufficiently cooked, it is sliced and served alone or together with a variety of sauces and vegetables [ 44 ]. The meat can come from different animal species, such as mutton, beef, chicken, or turkey, and include other ingredients such as salt, spices, onions, oil, milk and milk protein, eggs and egg powder, soy protein, and phosphate [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salah satu jenis bakteri yang banyak dihubungkan dengan kejadian foodborne disease pada kebab adalah Escherichia coli (E. coli) terutama strain E. coli O157:H7. The EU Rapid Alert System for Food and Feed (RASFF) mencatat 97 notifikasi kasus terkait kebab pada periode tahun 2000 sampai 2017 (Bonilauri et al 2018). Setiap tahun diperkirakan terjadi 265 000 kasus infeksi shiga toxin-producing E. coli (STEC) pada manusia di Amerika Serikat dan 36% diantaranya disebabkan oleh STEC O157 (CDC, 2014).…”
Section: Pendahuluanunclassified